MicroRNA Biosensors for Early Detection of Hepatocellular Carcinoma - Xiaogang Lin; Ke Wang; Chunfeng Luo; Mengjie Yang; Jayne Wu (Chemosensors, 2023)
Hepatocellular carcinoma (HCC) is the main pathological type of liver cancer. Due to its insidious onset and the lack of specific early markers, HCC is often diagnosed at an advanced stage, and the survival rate of patients with partial liver resection is low. Non-coding RNAs (ncRNAs) have emerged as valuable biomarkers for HCC detection, with microRNAs (miRNAs) being a particularly relevant class of short ncRNAs. MiRNAs play a crucial role in gene expression regulation and can serve as biomarkers for early HCC detection. However, the detection of miRNAs poses a significant challenge due to their small molecular weight and low abundance. In recent years, biosensors utilizing electrochemical, optical, and electrochemiluminescent strategies have been developed to address the need for simple, rapid, highly specific, and sensitive miRNA detection. This paper reviews the recent advances in miRNA biosensors and discusses in detail the probe types, electrode materials, sensing strategies, linear ranges, and detection limits of the sensors. These studies are expected to enable early intervention and dynamic monitoring of tumor changes in HCC patients to improve their prognosis and survival status.